Mitochondrial Dysfunction and Cardiovascular Disease: Pathophysiology and Emerging Therapies. (2nd August 2022) - Stamerra, Cosimo Andrea; Di Giosia, Paolo; Giorgini, Paolo; Ferri, Claudio; Sukhorukov, Vasily N.; Sahebkar, Amirhossein
Abstract : Mitochondria ensure the supply of cellular energy through the production of ATP via oxidative phosphorylation. The alteration of this process, called mitochondrial dysfunction, leads to a reduction in ATP and an increase in the production of reactive oxygen species (ROS). Mitochondrial dysfunction can be caused by mitochondrial/nuclear DNA mutations, or it can be secondary to pathological conditions such as cardiovascular disease, aging, and environmental stress. The use of therapies aimed at the prevention/correction of mitochondrial dysfunction, in the context of the specific treatment of cardiovascular diseases, is a topic of growing interest. In this context, the data are conflicting since preclinical studies are numerous, but there are no large randomized studies.